Relationship of Visceral Fat and Adipokines with Cardiometabolic Diseases in Psoriasis - Nasrin Goolam Mahyoodeen; Nigel J. Crowther; Lushen Pillay; Tracy Snyman; Marketa Toman; Sheetal Daya; Mohammed Tikly (Medical Journals Sweden, 2019)
As part of a larger cross-sectional, case-control study on cardiometabolic diseases in psoriasis this study investigated the association of visceral fat and serum adipokines with psoriasis and cardiometabolic diseases. A total of 103 patients with psoriasis and 98 controls, matched for body mass index, ethnicity and sex, were recruited over 15 months. Abdominal visceral fat was measured by computerized tomography. Logistic regression analysis revealed that visceral fat was associated with psoriasis (odds ratio (95% confidence interval): 1.56 (1.15, 2.11)), hypertriglyceridaemia (1.67 (1.22, 2.28)), low high-density lipoprotein (1.63 (1.19, 2.22)) and type 2 diabetes (1.77 (1.24, 2.54)), (p < 0.005 for all). These respective associations were linked to serum interleukin-6, adiponectin, tumour necrosis factor and insulin resistance. Psoriasis was associated with type 2 diabetes (7.94 (2.64, 23.9)), independent of visceral fat. These data suggest that visceral fat and its mediators play a key role in psoriasis-associated cardiometabolic diseases. Psoriasis itself is associated with an increased risk of type 2 diabetes.